2017
DOI: 10.1002/chem.201605668
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Excess Residual PbI2 on Photovoltaic Performance, Charge Separation, and Trap‐State Properties in Mesoporous Structured Perovskite Solar Cells

Abstract: Organic-inorganic halide perovskite solar cells have rapidly come to prominence in the photovoltaic field. In this context, CH NH PbI , as the most widely adopted active layer, has been attracting great attention. Generally, in a CH NH PbI layer, unreacted PbI inevitably coexists with the perovskite crystals, especially following a two-step fabrication process. There appears to be a consensus that an appropriate amount of unreacted PbI is beneficial to the overall photovoltaic performance of a device, the only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 62 publications
(55 reference statements)
1
52
0
Order By: Relevance
“…[50] The shift of the dynamic curve demarcation point represents the weightc hanges of the two dynamic components (i.e.,t he changes of the charge-carrier recombination process), which influences the photovoltaic performance of the perovskite devices.A ccordingly,j udiciousm odulation of the PbI 2 contents in perovskite phase may be ap otential strategy for the balance of the biphasic recombination process, as it can not only regulate the trap state distribution (k B T 0 ), but also alter the energyb arrier. It can be deduced that the demarcation point between perovskite-andT iO 2 -dominating recombination processes will shift when the characteristic energy of either phase changes, as the reciprocal of the characteristice nergy is correlated to the slope of the ln k r -V ph curve.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[50] The shift of the dynamic curve demarcation point represents the weightc hanges of the two dynamic components (i.e.,t he changes of the charge-carrier recombination process), which influences the photovoltaic performance of the perovskite devices.A ccordingly,j udiciousm odulation of the PbI 2 contents in perovskite phase may be ap otential strategy for the balance of the biphasic recombination process, as it can not only regulate the trap state distribution (k B T 0 ), but also alter the energyb arrier. It can be deduced that the demarcation point between perovskite-andT iO 2 -dominating recombination processes will shift when the characteristic energy of either phase changes, as the reciprocal of the characteristice nergy is correlated to the slope of the ln k r -V ph curve.…”
Section: Resultsmentioning
confidence: 99%
“…[37,50] Briefly,t he photoanode composes of ac ompact and mesoporous TiO 2 layer,w hich was made from aT i 2 + complex [i.e.,t itanium diisopropoxide bis(acetylacetonate) solution] and ac ommercial paste by using as pin-coating method. [37,50] Briefly,t he photoanode composes of ac ompact and mesoporous TiO 2 layer,w hich was made from aT i 2 + complex [i.e.,t itanium diisopropoxide bis(acetylacetonate) solution] and ac ommercial paste by using as pin-coating method.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that the surface of the stoichiometrically formed perovskite could be passivated by PbI 2 by increasing the annealing time, where a self‐induced passivation layer and perovskite were proposed to lead to type I band alignment that might reduce recombination at both the perovskite/ETL and perovskite/HTL interfaces . Nevertheless, it was argued that excess PbI 2 might have an adverse effect, thus a careful control of quantity of PbI 2 is critical for device performance. A three‐fold increase in charge diffusion length was observed when 2.5 wt % excess PbI 2 was used, compared with stoichiometric MAPbI 3 …”
Section: Interfacial Engineering In the Normal Structurementioning
confidence: 99%
“…Because perovskite films with a larger amount of residual PbI 2 have been considered to have a larger amount of trap sites, which induce nonradiative carrier recombination, 15,29,30 the sample with a smaller amount of PbI 2 should show higher PL intensity. Our result suggests that the PS nanopores contributed to the enhancement of radiative recombination by decreasing the efficiency of electron extraction at the perovskite/compact-TiO 2 interface and spatially confining carriers within the small regions, regardless of the residual PbI 2 .…”
mentioning
confidence: 99%
“…29,30 In summary, carrier dynamics in templated perovskite films with different number densities of nanopores were investigated. Steady-state PL measurement confirmed that the efficiency of electron extraction is significantly decreased by PS nanopores due to the decrease in the surface coverage of perovskite on a compact TiO 2 layer.…”
mentioning
confidence: 99%